FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HEMORAGIC POST PARTUM DI PUSKESMAS SUMBER MARGA TELANG - Dian Novita; Amlah Amlah; Eka Afrika (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
Postpartum hemorrhage is bleeding that is more than 500 ml (in vaginal delivery) or more than 1000 ml (in caesarean delivery), WHO (World Health Organization) Regarding national health status in achieving the Sustainable Developmentd Goals (SDGs) target globally, around 830 women died every day due to complications of pregnancy and childbirth with an MMR rate of 216/100,000 live births. The purpose of this study was to determine the relationship between preeclampsia, pregnancy spacing and birth weight of babies simultaneously with postpartum hemorrhage in the work area of ​​Sumber Marga Telang Public Health Center, Banyuasin Regency in 2020. This study uses an analytical survey method with a cross sectional approach, the independent variables (preeclampsia, gestational interval and birth weight) and the dependent variable (the incidence of Postpartum Hemorrhage). This study uses secondary data by viewing and recording data from medical records using a Check List. The results of the chi-square test of the preeclampsia variable obtained value = 0.001 smaller than = 0.05, the variable duration of pregnancy obtained value = 0.044 and the BBRL variable obtained value = 0.00405 indicating there is a significant relationship between preeclampsia, pregnancy distance and BBRL with post partum hemorrhoids in the Work Area of ​​the Sumber Marga Telang Health Center, Banyuasin Regency in 2020    Keywords         : LBW, Pregnancy Distance, Preeclampsia, Post Partum Hemorrhage